Hot-Melt Extrusion (HME) Is Advanced Approach for Development of Solid Self Emulsifying Drug Delivery System - Jamil, Shahid; Sadeq, Tariq Waece; Samad, Abdul (International Journal of Membrane Science and Technology, 2023)
The pharmaceutical industry is paying more and more attention to hot-melt extrusion (HME), but this technology’s promise for creating solid self-emulsifying drug delivery systems (S-SMEDDS) has not yet been fully realized. The numerous published publications over the past five years show that hot melt extrusion (HME) technology is increasingly being used for novel applications. Because it has low-cost scale-up capabilities and process automation, which reduce labour costs and capital expenditure. HME has become a crucial technique for pharmaceutical manufacturing and research applications involving drug delivery. In the development of new drug delivery systems, the novel use of the HME method offers a promising alternate strategy. Through a discussion of pertinent case studies, the current review examines the value of HME in the creation of innovative drug delivery systems.